Recommendations for Statistical Reporting in Cardiovascular Medicine: A Special Report From the American Heart Association. Issue 4 (27th July 2021) - Althouse, Andrew D.; Below, Jennifer E.; Claggett, Brian L.; Cox, Nancy J.; de Lemos, James A.; Deo, Rahul C.; Duval, Sue; Hachamovitch, Rory; Kaul, Sanjay; Keith, Scott W.; Secemsky, Eric; Teixeira-Pinto, Armando; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Statistical analyses are a crucial component of the biomedical research process and are necessary to draw inferences from biomedical research data. The application of sound statistical methodology is a prerequisite for publication in the American Heart Association (AHA) journal portfolio. The objective of this document is to summarize key aspects of statistical reporting that might be most relevant to the authors, reviewers, and readership of AHA journals. The AHA Scientific Publication Committee convened a task force to inventory existing statistical standards for publication in biomedical journals and to identify approaches suitable for the AHA journal portfolio. The experts on the task force were selected by the AHA Scientific Publication Committee, who identified 12 key topics that serve as the section headers for this document. For each topic, the members of the writing group identified relevant references and evaluated them as a resource to make the standards summarized herein. Each section was independently reviewed by an expert reviewer who was not part of the task force. Expert reviewers were also permitted to comment on other sections if they chose. Differences of opinion were adjudicated by consensus. The standards presented in this report are intended to serve as a guide for high-quality reporting of statistical analyses methods and results.